WARALABA SEBAGAI PELUANG BARU DALAM DUNIA WIRAUSAHA - Oktaviani, Ni Made Ayu Dwi (Waisya : Jurnal Ekonomi Hindu, 2024)
Franchising is a new choice in the development of the business world amid the development of industry 5.0. Franchising is developed a business system in which a brand owner or company (franchisor) gives the right to another party (franchisee) to sell products or services using a trademark, operational system, and support that has been proven successful This research uses a quantitative approach with data collection using literature studies. researchers explore various available sources of information, such as journal articles, textbooks, and other related documents. Data analysis was carried out by data reduction, data presentation and conclusion. Presentation of the analysed data is done in a descriptive narrative that is adjusted to the level of the researcher's ability. The results of the study show that franchising is currently an option for prospective entrepreneurs. Franchising as an entrepreneurial business model offers advantages such as support from the franchisor, access to a recognised brand, and flexibility, but its success depends on a SWOT analysis that includes brand strength, franchisor support, expansion opportunities, and competitive threats. Factors such as brand quality, franchisor support, efficient management, innovation and the role of government regulation also influence the success of franchising, with complex social, economic and environmental impacts, but with attention to all these aspects, franchising can be an engine of inclusive and sustainable growth in Indonesia.